Implementación de un banco para ensayos de impacto en vidrios planos templados de seguridad usados en edificios - Eusebio Teherán, Robert Nick (2015)
This thesis aims to implement a bank for impact testing in flat tempered safety glass, based on American Technical Standard ANSI Z97.1, the purpose is to certify the tenacity minimum requirements to be met by flat tempered glass for buildings sold in different countries. Among the specific objectives geometric parameters have been determined, involving greater efficiency and reliability to the construction of the different parts of the bank for testing, this implementation will consist of a beam structure in "C", welded and anchored in a fixed base concrete, to avoid any kind of vibrations. The manufacture of the impactor shall be pear shaped, leather-wrapped and inside will have lead spheres with diameters in the order of 2.5 mm, with a total weight of 45 kg., which exercise the impact from tempered glass at three different heights depending on the quality, classification and certification. The tests provided are defined according to the table procedures of ANSI Z97.1-2009, with calibrated equipment and instruments indicated in the standard, in order to optimize the impact test. Table with procedures for certification of temperate flat glass which provides ANSI Z97.1- 2009, is available in an analytical way of testing, testing and certifying the quality of tempered glass under the ANSI Z97.1 standard -2009.